2018
DOI: 10.1371/journal.pone.0195253
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and testing of a Raman hyperspectral imaging system to reveal powdered food adulteration

Abstract: The potential adulteration of foodstuffs has led to increasing concern regarding food safety and security, in particular for powdered food products where cheap ground materials or hazardous chemicals can be added to increase the quantity of powder or to obtain the desired aesthetic quality. Due to the resulting potential health threat to consumers, the development of a fast, label-free, and non-invasive technique for the detection of adulteration over a wide range of food products is necessary. We therefore re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…Most recently, Raman imaging on both the micro- and macroscale levels have been successfully tested for powdered food authenticity analysis [13,14,15,16,17,18,19]. Since a laser beam can penetrate a certain depth into a sample, the penetration depth was first determined to ensure that the adulterant particles at the very bottom of the sample could be detected [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Raman imaging on both the micro- and macroscale levels have been successfully tested for powdered food authenticity analysis [13,14,15,16,17,18,19]. Since a laser beam can penetrate a certain depth into a sample, the penetration depth was first determined to ensure that the adulterant particles at the very bottom of the sample could be detected [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Lohumi et al. () showed that there is a linear correlation between the peaks obtained by Raman spectroscopy (785 nm) and the amount of the adulterants Sudan I ( R = 0.989) and Congo red ( R = 985) in paprika at concentrations between 0.05% and 1%. Bivariate analysis (two‐band image) compared to a single band image showed better results for the visualization and quantification of the adulterants Sudan I (1227 and 1493 cm −1 ) and Congo red (1351 and 1451 cm −1 ).…”
Section: Nontargeted Analytical Methodsmentioning
confidence: 99%
“…Polynomial fitting algorithm is used for removing fluorescence background signal and baseline in Raman spectra (Lieber & Mahadevan‐Jansen, ), and this algorithm was used for treated Raman spectra of paprika/Sudan I (Monago‐Maraña et al., ), chili pepper/Sudan I (Haughey et al., ), and turmeric/metanil yellow (Dhakal et al., ). In Raman HSI, fluorescence background signals could be corrected using the adaptive iteratively reweighted penalized least squares (airPLS) method (Lohumi et al., ; Zhang, Chen, & Liang, ). In addition, 2D‐median filter could be applied to remove high‐intensity spikes (Bocklitz, Guo, Ryabchykov, Vogler, & Popp, ).…”
Section: Chemometrics For Spice Authenticationmentioning
confidence: 99%
“…El prototipo de medición de color para uso en vegetales frescos fue construido y evaluado en el Laboratorio de Frutas y Hortalizas de la Universidad Nacional de Colombia, Sede Palmira. El prototipo consistió en una caja con dimensiones 20 cm x 20 cm x 20 cm y paredes de color negro, lo cual fue definido siguiendo las investigaciones efectuadas por Tarlak et al (2016) y Lohumi et al (2018). Se adaptaron el sensor de temperatura DHT11 en la base y el sensor de color TCS230-3200 que incluía LEDs, por encima del material a evaluar.…”
Section: Construcción Del Prototipounclassified